Representaciones Sociales de los Desmovilizados de las FARC en ARMENIA, Sobre el Beneficiode Atención Psicosocial Brindado por la Agencia Colombiana para la Reintegración (ACR) (2016)
This research shows the social representations created by demobilized around the Psychosocial Care benefit offered by the Colombian Agency for Reintegration (ACR). At 5 the same time the importance of this for the demobilized assume the barriers in society are evident. Research in knowledge that have demobilized over the target that has this benefit is evident. This knowledge has allowed former combatants understand and explain their realities constituting a clear and definite social representation.